Socio-Emotional Competence and Self-Efficacy of Future Secondary School Teachers - Romero-García Carmen; Buzón-García Olga; Marcano Beatriz (MDPI AG, 2022)
The assessment and development of teachers' socio-emotional competence has become a topic of interest in education. Within the classroom, this competence is demonstrated not only in teaching but also in student development. The present study addressed the relationship between socio-emotional competence and self-efficacy, as perceived by prospective secondary-school teachers (n = 285) studying for a master's degree in teacher training, and possible differences according to the socio-demographic characteristics of the sample. A descriptive, correlational and cross-sectional, survey-type method was followed. The instruments used were a previously validated socioemotional competence inventory, and an adapted version of the Teachers Self Efficacy Scale. The results showed an adequate level in most of the socio-emotional competencies studied and a high perception of self-efficacy, and both scales correlated positively. Higher levels of socioemotional competence were found in women and in teachers aged 40 to 50 with more teaching experience. The positive effect of experience in relation to self-efficacy being higher in women than in men was corroborated. We concluded that there is a need to develop the socio-emotional competence of trainee teachers to improve their teaching performance.